Novel Method for the Determination of Preservative (Formaldehyde) in Bovine Milk through Smart Phone-Based Colorimetric Technology - Gupta, Vipin K; Aulakh, RS; Tomar, SS (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
The use of formaldehyde as a preservative is a very common practice to decrease the microbial load and to increase the shelf life of  the milk. Its addition in food has immense adverse public health significance. The present study explored a simple, low-cost, rapid,  reproducible, and field applicable Smartphone-based colorimetric technology, which was standardized and in-house validated for  the quantitative determination of formaldehyde in milk samples. The method has simple steps of spot-test reaction and digital image  analysis with the Red Green Blue approach. The linearity of the method was shown by analytical curves ranging from 0.25–4 ppm that  were characterized by R2 > 0.99. The limit of detection of 0.31 ppm demonstrated the sensitivity of the method to estimate formaldehyde  residues in milk. Thus, we developed an innovative technology that uses an easily available device with potential of on-site quantification  of formaldehyde in the supply chain. This technique is not only beneficial for end-users but also helps in achieving extension goals,  which emphasize on the transfer of technology, i.e., moving out of the lab to the land.
Keywords: Formaldehyde; Milk; Preservative; Quantification; Smartphone-based colorimetry